Evaluation of energy generation potentil of municipal solid waste in Ibadan (2015)
Waste of energy (WTE) is a renewable and environmentally sound process that has been proven to provide reliable electricity generation in developed and developing nations. This study was carried out to evaluate the WTE potential of municipal solid waste (MSW) in Ibadan metropolis, Characterization, and proximate analysis of representative MSW samples collected in year 2014 at two dumpsites (Ajakanga and Aba Eku) were carried out in accordance with standard procedures. Food wastes constituted 39%, the highest component of the MSW The net calorific value was evaluated to be 22.5 MJ/kg. The energy potential per annum was evaluated as 2d GW for approximate total waste of 447 thousand tones generated and disposed in Ibadan in year 2012. The energy potential in MSW could be harnessed to address the energy shortfall in the city